Desiring Revolution II. Issue 1 (April 2015) - Elmarsafy, Ziad
<x xml:space="preserve">Abstract</x> Where do revolutions come from? Where do they begin? How are we to understand, and where should we locate, the beginnings of the Egyptian Revolution of 25 January 2011? These are the questions at the heart of this essay. After a survey of the ideas of Hannah Arendt on revolution, Jacques Derrida on the messianic and Ernst Bloch and Herbert Marcuse on the intersection between desire and political action, selected works by Naguib Mahfouz (The Day the Leader Was Killed, Morning and Evening Talk) and Gamal al-Ghitani (The Za'farani Files) are read as texts with a prognostic value, ones that emit signs of the revolution to come. Through the repeated pattern of failures of desire that recurs frequently in novels written during the presidencies of Anwar Sadat and Hosni Mubarak, the conditions of impotence and anhedonia associated with the advent of capitalism become symptomatic of a dysfunctional and hopelessly corrupt society. In this framework, the articulation of desire becomes the first step towards revolution.